Pengembangan Karakter Siswa Dan Kemampuan Berpikir Kreatif Melalui Pembelajaran Cooperative Integrated Reading And Composition (CIRC) Yang Terintegrasi Dalam Pembelajaran Kimia - Rizka Anggraeni; Khaeruman Khaeruman; Raehanah Raehanah (Universitas Pendidikan Mandalika Mataram, 2014)
This study aims to determine character of student after learning CIRC and effect of CIRC learning to creative thinking skills on atomic structure and the periodic system of unsure matter. This research used an experimental method, the type of quasi experiment with Pretest-posttest control group design. Sample consists of 2 class of experiment class (CIRC learning) and control class (a lecture and question and answer) were selected by Cluster Sampling. Data retrieval research using observation sheet for character development and for creative thinking skills using the form of description test. Data on the observation of student character shows the character of students do not get better after learning CIRC compared with a lecture and question and answer on atomic structure of matter and the periodic system of unsure, as looking the average value of the experiment class is 76,97 lower than the control class is 79,12. Data analysis for hypothesis using u-test with SPSS 15.0 for Windows. Based on data analysis get significant value (0,166) > significant a (0,05). It can be concluded that there is no effect CIRC learning to creative thinking skills on atomic structure of matter and the periodic system of unsure.